Bullet Proof? Program Evaluation in Conflict Areas: Evidence from Rural Colombia - Nina Wald; Carlos Bozzoli (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2011)
Recently, Conditional Cash Transfer Programs (CCT) became increasingly popular in developing countries due to their positive outcomes on health and education. In this paper, we are particularly interested in testing if children participating in CCT (treated) in conflict affected regions benefit more (or less) than their counterparts in peaceful areas. To test this, we combine longitudinal CCT data from Colombia with a conflict event dataset. This allows us to use standard techniques in treatment evaluation, but it augments the testing equations by adding interactions between dummies identifying different groups and indicators of violence. We find that the CCT program had an extra benefit in conflict areas concerning enrolment. However, grade progression is similar for treated children in low and high conflict regions. Results suggest that the program may work in attracting children to school, but in high conflict regions children tend to do less homework and miss more days in school.
Keywords: C23; D74; I21; I38; O54; 330; Conditional Cash Transfer Program; Education; Conflict; Colombia; Panel Data; Treatment Effects